Insightful Backbone Modifications Preventing Proteolytic Degradation of Neurotensin Analogs Improve NTS1-Induced Protective Hypothermia - Previti, Santo; Vivancos, Mélanie; Rémond, Emmanuelle; Beaulieu, Sabrina; Longpré, Jean-Michel; Ballet, Steven; Sarret, Philippe; Cavelier, Florine (Frontiers in Chemistry, 2020)
Therapeutic hypothermia represents a brain-protective strategy for multiple emergency situations, such as stroke or traumatic injury. Neurotensin (NT), which exerts its effects through activation of two G protein-coupled receptors, namely NTS1 and NTS2 induces a strong and long-lasting decrease in core body temperature after its central administration. Growing evidence demonstrates that NTS1 is the receptor subtype mediating the hypothermic action of NT. As such, potent NTS1 agonists designed on the basis of the minimal C-terminal NT(8-13) bioactive fragment have been shown to produce mild hypothermia and exert neuroprotective effects under various clinically relevant conditions. The high susceptibility of NT(8-13) to protease degradation (half-life < 2 min) represents, however, a serious limitation for its use in pharmacological therapy. In light of this, we report here a structure-activity relationship study in which pairs of NT(8-13) analogues have been developed, based on the incorporation of a reduced Lys8-Lys9 bond. To further stabilize the peptide bonds, a panel of backbone modifications was also inserted along the peptide sequence, including Sip10, D-Trp11, Dmt11, Tle12 and TMSAla13. Our results revealed that the combination of appropriate chemical modifications leads to compounds exhibiting high affinity for NTS1 (Ki = 20 pM; 3) and improved resistance to proteolytic cleavages (> 24 hours; 16). Among them, the NT(8-13) analogues harboring the reduced amine bond combined with the unnatural amino acids TMSAla13 (4), Sip10 (6) or the di-substitution Lys11 - TMSAla13 (12), D-Trp11 - TMSAla13 (14) and Dmt11 - Tle12 (16) produced sustained hypothermic effects (-3°C for at least 1 hour). Importantly, we also observed that NTS1-mediating hypothermia was mainly driven by the increased stability of the NT(8-13) derivatives, instead of the high binding affinity at NTS1. Altogether, these results reveals the importance of the reduced amine bond in optimizing the metabolic properties of the NT(8-13) peptide and support the development of stable NTS1 agonists as first drug-candidate in neuroprotective hypothermia.